Predator’s Bite Disrupting Child’s Parotid Duct - Mekhaeel, Shehata Fakhry Mekhaeel; Salem, Mohamed Ahmed Eissa Sameh; Protasov, Vitalevitch Andrey; Taha, Nada Ahmed Mohamed Elsayed; Omar Kamal Sandouka; Sohaila Mahmoud Said Mahmoud; Atheer Alwan Albulanee; Ali Hatem Ali Mohamed (Medical Science: Trends and Innovations Vol. 13, 2025)
Biting is a normal behavior of animals and about 2% of the population is bitten annually by animals. Being in general more common among males, still animal bits have sex predilection; cat bites are commoner among females, whilst dog bites are abundant among males In spite of being rare in comparison to the incidence of dog bites, wolf bites are seen among the inhabitants of rural and rugged mountainous areas which are the natural shelter areas for such predators. The victims’ age also contributes to the epidemiology of animal facial bites; Children have an increased chance of being bitten on the face due to shorter stature, the disproportionate size of their head relative to their body making it a larger target, a less well-developed motor skills which are needed to defend themselves with their extremities, in addition, children are less likely to be able to recognize the emotional behavior of animals so, they do not probably evaluate the danger and may be more prone to provoking the animal. Therefore, the incidence of animal facial bites is much more common in children in comparison to adults (75%:10%) respectively. Animal facial bites involve mostly the lips, nose and cheeks. Bite wounds are considered complex contaminated injuries requiring an appropriate treatment plan. The most common complication of animal bites is wound contamination by gram-positive and gram-negative microorganisms as well as salivary complications; salivary fistula.